2006
DOI: 10.1017/s1138741600006168
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Structures of Photographic and Stereoscopic Spaces

Abstract: Two experiments were conducted to investigate the geometrical structures of photographic and stereoscopic spaces. In Experiment 1, it was investigated how accurately photographic space reproduces real physical space, and the geometrical structure of photographic space was compared with that of visual space. As a result, the mapping function of distance between photographic and physical spaces (δ = ad b ) shows that a and b range from 0.96-1.1 and 0.69-0.78. The mapping function of angle between photographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(35 reference statements)
0
2
0
4
Order By: Relevance
“…Hagen, Jones, and Reed (1978), Takezawa (2005), and Watanabe (2004Watanabe ( , 2006 indicated that apparent depth in a picture is compressed as compared to apparent depth in ordinary environments (cf. Hecht, van Doorn, & Koenderink, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Hagen, Jones, and Reed (1978), Takezawa (2005), and Watanabe (2004Watanabe ( , 2006 indicated that apparent depth in a picture is compressed as compared to apparent depth in ordinary environments (cf. Hecht, van Doorn, & Koenderink, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Watanabe (2006), representar o espaço através de fotografias é equivalente a representá-lo por meio de desenhos gerados no computador, pois ambas encerram propriedades não-euclidianas (hiperbólicas) do espaço visualmente percebido. Além disso, outros estudos sugerem que a percepção de tamanho e a percepção de distância são afetadas da mesma maneira em fotografias e no ambiente real ) e que as distorções do espaço observadas em ambos são similares .…”
Section: Gradiente De Texturaunclassified
“…Estas informações eram provenientes de desenho gerado computacionalmente ou de fotografia com elementos naturais. Segundo Watanabe (2006) (Chelazzi, 1999), o que repercute na dificuldade em ignorar estas informações numa tarefa de comparar tamanhos .…”
Section: Discussão Geralunclassified
See 2 more Smart Citations